Occurrence of culturable soil fungi in a tropical moist deciduous forest Similipal Biosphere Reserve, Odisha, India - Jena, Santanu K. (Braz J Microbiol, 2015)
Similipal Biosphere Reserve (SBR) is a tropical moist deciduous forest dominated by the species Shorea robusta . To the best of our knowledge their rich biodiversity has not been explored in term of its microbial wealth. In the present investigation, soil samples were collected from ten selected sites inside SBR and studied for their physicochemical parameters and culturable soil fungal diversity. The soil samples were found to be acidic in nature with a pH ranging from of 5.1–6.0. Highest percentage of organic carbon and moisture content were observed in the samples collected from the sites, Chahala-1 and Chahala-2. The plate count revealed that fungal population ranged from 3.6 × 10 (4) –2.1 × 10 (5) and 5.1 × 10 (4) –4.7 × 10 (5) cfu/gm of soil in summer and winter seasons respectively. The soil fungus, Aspergillus niger was found to be the most dominant species and Species Important Values Index (SIVI) was 43.4 and 28.6 in summer and winter seasons respectively. Among the sites studied, highest fungal diversity indices were observed during summer in the sites, Natto-2 and Natto-1. The Shannon-Wiener and Simpson indices in these two sites were found to be 3.12 and 3.022 and 0.9425 and 0.9373 respectively. However, the highest Fisher’s alpha was observed during winter in the sites Joranda, Natto-2, Chahala-1 and Natto-1 and the values were 3.780, 3.683, 3.575 and 3.418 respectively. Our investigation revealed that, fungal population was dependent on moisture and organic carbon (%) of the soil but its diversity was found to be regulated by sporulating species like Aspergillus and Penicillium .